Study of some structural , optical , Electrical Properties of CdS thin films deposited by chemical Spray Pyrolysis Method (Baghdad Science Journal, 2009)
In this research we prepared CdS thin films by Spray pyrolysis method on a glass substrates and we study its structural , optical , electrical properties .The result of (X-Ray ) diffraction showed that all thin films have a polycrystalline structure , The relation of the transmission as a function of wavelength for the CdS films had been studied , The investigated of direct energy gap of the CdS its value is (2.83 eV). In Hall effect measurement of the CdS we find the charge carriers is p – type and Hall coefficient 1157.33(cm3/c) ,Hall mobility 6.77(cm2/v.s)